Pharmaceutical Counseling Has a Positive Impact on Quality of Life of Hypertension Patients - Aulia, Gina; Halimah, Eli; Lestari, Keri (Pharmacology and Clinical Pharmacy Research)
Pharmacists play a major role in educating patients regarding drug therapy, in order to achieve optimal health outcomes. The aim of this study was to investigate the effect of pharmaceutical counseling on quality of life (QoL) of hypertensive patients with renal impairment at one of public hospital in Bandung, Indonesia. This study used a prospective experimental design with pretest-posttest design for 2 months. Inclusion criteria in this study were hypertensive patients with renal impairment who received antihypertensive drugs, aged >18 years, and signed the informed consent. Exclusion criteria were patients who were not able to fill in the questionnaire, patients with end stage renal diseases, diabetes, and pregnant or lactating patients. Pharmaceutical counseling was given during 2 months of the therapy. Pharmaceutical counseling consisted of education on the appropriate use of drugs and disease management. Schedule of their own medication and leaflet containing educational information were given to the subjects. QoL was assessed using a previously validated Mini-Questionnaire of QoL in Arterial Hypertension (MINICHAL). The questionnaire consisted of 16 two dimensions questions, i.e., mental health and somatic manifestation. We found that the mean increase in mental health status (49.5Â±5.3) was higher than that of somatic dimension (32.7Â±3.6). Both dimensions had statistically significant improvement (P value <0.05). In conclusion, pharmaceutical counseling is beneficial to improve QoL of hypertension patients.Keywords: hypertension, renal impairment, quality of lifeÂ